Synovial Mesenchymal Stem Cells Promote Meniscus Regeneration Augmented by an Autologous Achilles Tendon Graft in a Rat Partial Meniscus Defect Model. (21st May 2015) - Ozeki, Nobutake; Muneta, Takeshi; Matsuta, Seiya; Koga, Hideyuki; Nakagawa, Yusuke; Mizuno, Mitsuru; Tsuji, Kunikazu; Mabuchi, Yo; Akazawa, Chihiro; Kobayashi, Eiji; Saito, Tomoyuki; Sekiya, Ichiro
Abstract: Although meniscus defects and degeneration are strongly correlated with the later development of osteoarthritis, the promise of regenerative medicine strategies is to prevent and/or delay the disease's progression. Meniscal reconstruction has been shown in animal models with tendon grafting and transplantation of mesenchymal stem cells (MSCs); however, these procedures have not shown the same efficacy in clinical studies. Here, our aim was to investigate the ability of tendon grafts pretreated with exogenous synovial‐derived MSCs to prevent cartilage degeneration in a rat partial meniscus defect model. We removed the anterior half of the medial meniscus and grafted autologous Achilles tendons with or without a 10‐minute pretreatment of the tendon with synovial MSCs. The meniscus and surrounding cartilage were evaluated at 2, 4, and 8 weeks ( n = 5). Tendon grafts increased meniscus size irrespective of synovial MSCs. Histological scores for regenerated menisci were better in the tendon + MSC group than in the other two groups at 4 and 8 weeks. Both macroscopic and histological scores for articular cartilage were significantly better in the tendon + MSC group at 8 weeks. Implanted synovial MSCs survived around the grafted tendon and native meniscus integration site by cell tracking assays with luciferase+, LacZ+, DiI+, and/or GFP+ synovial MSCs and/or GFP+ tendons. Flow cytometric analysis showed that transplanted synovial MSCs retained their MSC properties at 7 days and host synovial tissue also contained cells with MSC characteristics. Synovial MSCs promoted meniscus regeneration augmented by autologous Achilles tendon grafts and prevented cartilage degeneration in rats. Stem Cells 2015;33:1927–1938